(untitled) (BIRDEM Medical Journal, 2021)
Primary intraosseous meningioma (PIM) is a rare form of meningioma, a benign lesion of the meninges. Imaging evaluation of a patient with frontoparietal scalp swelling revealed an osteoblastic intracalvarial lesion. Following surgical resection, the histological examination revealed an intra-osseous meningioma. Birdem Med J 2021; 11(2): 133-136